Proximity-induced topological state in graphene - SANVITO, STEFANO (My University, 2014)
The appearance of topologically protected states at the surface of an ordinary insulator is a rare occurrence and to date only a handful of materials are known for having this property. An intriguing question concerns the possibility of forming topologically protected interfaces between different materials. Here we propose that a topological phase can be transferred to graphene by proximity with the three-dimensional topological insulator Bi2Se3. By using density functional and transport theory, we prove that, at the verge of the chemical bond formation, a hybrid state forms at the graphene/Bi2Se3 interface. The state has Dirac-cone-like dispersion at the Γ point and a well defined helical spin texture, indicating its topologically protected nature. This demonstrates that proximity can transfer the topological phase from Bi2Se3 to graphene.
PUBLISHED
Keywords: Topological insulators (TIs); Nanoscience & Materials